Teaching, Research and Academic Careers An Analysis of the Interrelations and Impacts - Checchi, Daniele; Jappelli, Tullio; Uricchio, Antonio (Springer International Publishing : Imprint: Springer, 2022)
VI, 358 p. 1 illus.